SWOT Analysis of BUMN Banks After Merger to Become Indonesian Sharia Bank (Study at BSI KCP Tomoni, East Luwu Regency) - Hamida Ambas (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This thesis discusses the SWOT Analysis of Post-Merger BUMN Banks to Become Indonesian Sharia Banks (Study on BSI KCP Tomoni, East Luwu Regency). The main problem in this study is how the strengths, weaknesses, opportunities and threats of Bank Syariah Indonesia Tomoni KCP East Luwu Regency and what strategies the bank needs to implement. This study aims to find out and analyze the strengths, weaknesses, opportunities, and threats and what strategies can be applied to the Indonesian Sharia Bank KCP Tomoni, East Luwu Regency. This type of research is descriptive qualitative. Sources of research data were obtained from direct interviews with BSI KCP Tomoni employees, BSI KCP Tomoni customers, and one of the academics, using observation, interview and documentation techniques. The data analysis technique used is the SWOT analysis technique, then followed by drawing conclusions and verification. From the results of this study, it can be seen that BSI has many opportunities that need to be utilized as best as possible. Therefore, BSI needs to improve and add new strategies to the SO strategy, WO strategy, ST strategy and WT strategy